Integrating Problem-Based Learning in Improving Speaking Skills of Seventh Grade Students at Bala Keselamatan Christian Junior High School Palu - Latuasan, Willda Angelica; Kamaruddin, Abd; Maf’ulah, Maf’ulah; Nadrun, Nadrun (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the effectiveness of Problem-Based Learning (PBL) in enhancing the speaking abilities of seventh-grade students at SMP Kristen BK Palu. It focuses on common challenges experienced by Indonesian EFL learners, particularly in terms of fluency, accuracy, and comprehensibility in oral communication. The research applied a quasi-experimental method using a non-equivalent control group pre-test–post-test design. The population included all seventh-grade students in the 2025/2026 academic year, with two existing classes selected as samples: Class 7A as the experimental group and Class 7B as the control group. The experimental group was taught using the PBL approach, while the control group received conventional teacher-centered instruction. Data were gathered through speaking tests conducted before and after the treatment period. Students’ performances were assessed using an analytical rubric measuring fluency, accuracy, and comprehensibility. The findings revealed a significant improvement in the experimental group’s speaking scores, which increased from a mean of 4.50 in the pre-test to 10.60 in the post-test. Meanwhile, the control group showed no notable progress, maintaining a mean score of 4.65. The independent sample t-test yielded a calculated value of 14.55, exceeding the critical value of 2.005 at a 0.05 significance level (df = 54). These results indicate a statistically significant difference between the groups, confirming the positive impact of PBL. Overall, the study suggests that PBL fosters interactive, collaborative learning, promotes active engagement, and improves students’ confidence in speaking English.